A model of self-evaluation of careers in Higher Education from the perspective of the curriculum as a living organism (Revista Electrónica Calidad en la Educación Superior, 2021)
It is time to think complexly and transcend the current models of university career self-evaluation, understanding that the curriculum is a living system and, as such, it is dynamic and influenced by the people who participate in it. This article proposes a self-assessment and improvement model from this perspective, built within the framework of the research “Curricular quality: creation of a self-assessment model for the careers taught at the Sede del Atlántico of the University of Costa Rica (UCR)”. The qualitative and interpretive research focused on processes and explanations as well as the creation of the self-assessment model, in which teachers, administrators and students participated in the process.
Keywords: Self-assessment model; Higher Education; Education; Pedagogy